Integrating the role of community and mobile health in preventing risk factors for cardiovascular disease: a systematic review and meta-analysis of randomized controlled trials - Alparisi, Bima Diokta; Herman, Daniel; Amanda, Samira; Ihsan, M.; Suyanto; Irwan; Nurhasanah (Universitas Gadjah Mada, 2025)
Purpose: Cardiovascular disease (CVD) continues to be the primary cause of global morbidity and mortality, predominantly attributable to modifiable risk factors such as unhealthy diets, physical inactivity, and so on. While behavioral interventions are critical, the effective implementation of prevention strategies is often hindered by resource limitations. The integration of community-based strategies with mobile health (mHealth) technologies presents a promising approach for scalable, personalized risk mitigation. This review evaluates the efficacy of community-integrated mHealth inter- ventions in reducing CVD risk factors. Methods: We searched multiple databases for randomized controlled trials (RCTs) published over the last 10 years. Fourteen RCTs (n = 9,862 participants) met inclusion criteria, with interventions combining mHealth tools and community components. The risk of bias was assessed using the Cochrane RoB 2.0 tool, and meta-analyses were conducted using RevMan 5.4. Results: mHealth and community have demonstrated considerable efficacy in diminishing various cardiovascular risk factors. The primary mechanisms include enhanced adherence to a healthy lifestyle, continuous monitoring, and improved access to health-related information. The results of the meta-analysis are directly proportional to the findings, which significantly reduce the risk factors for heart disease: healthy dietary patterns (p < 0.0001), physical activity (p = 0.04), BMI (p = 0.002), systolic blood pressure (p = 0.002), and diastolic blood pressure (p = 0.02). However, total cholesterol and fasting blood sugar did not have significant results, namely (p=0.23) and (p=0.77). Conclusion: Community-integrated mHealth is an effective strategy for addressing CVD risk factors.